2021
DOI: 10.1108/jmlc-09-2021-0103
|View full text |Cite
|
Sign up to set email alerts
|

The international fraud triangle

Abstract: Purpose Fraud omnipresent in the media, the corporate world and the academic literature has attracted a great deal of research interest. Fraud and its various types and forms have been characterized as significant contributing factors to the development of severe financial crises. Recurrent financial crimes in both the private and the public sectors remind us that fraud and its negative consequences paralyze economic entities all over the world. Understanding the multidimensional nature of fraud is key to prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 95 publications
0
8
0
Order By: Relevance
“…In the academic setting, students may have the opportunity to cheat on exams, plagiarize work or falsify data. Previous researchers have demonstrated that when there is an opportunity to commit fraud with no possibility of detection or consequences, the likelihood of fraud increases among those who engage in such behavior (Cheliatsidou et al , 2023; Homer, 2020; Sánchez-Aguayo et al , 2021; Tickner and Button, 2021).…”
Section: Literature Review Research Model and Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In the academic setting, students may have the opportunity to cheat on exams, plagiarize work or falsify data. Previous researchers have demonstrated that when there is an opportunity to commit fraud with no possibility of detection or consequences, the likelihood of fraud increases among those who engage in such behavior (Cheliatsidou et al , 2023; Homer, 2020; Sánchez-Aguayo et al , 2021; Tickner and Button, 2021).…”
Section: Literature Review Research Model and Hypotheses Developmentmentioning
confidence: 99%
“…The fraud triangle theory was developed by criminologist Dr Donald Cressey in the 1950s. It is based on his research into white-collar crimes and embezzlement by trusted individuals (Cheliatsidou et al, 2023;Tickner and Button, 2021;Wardani and Putri, 2023). The theory has been widely adopted and applied in various fields, including accounting, auditing and criminology, to understand and prevent fraud (Burke and Sanney, 2018;Free, 2015;Homer, 2020;Said et al, 2017;S anchez-Aguayo et al, 2021).…”
Section: Literature Review Research Model and Hypotheses Developmentmentioning
confidence: 99%
“…Previous research has been proficient in studying fraudulent financial reporting (Cooper, Dacin and Palmer, 2013; Gullkvist and Jokipii, 2013; Johnson, Grazioh and Jamal, 1993; Maulidi and Ansell, 2020; Kassem, 2021; Navarrete and Gallego, 2022; Palmer, 2018; Morales, Gendron and Guénin-Paracini, 2014; Ratzinger-Sakel and Tiedemann, 2022; Saluja et al , 2021). Similarly, many studies address the concept of the fraud triangle, comprising three conditions for fraud, namely: motive/pressure, opportunity and rationalization, as well as several possible other conditions for fraud (Cheliatsidou et al , 2023; Homer, 2020; Kagias et al , 2022; Maulidi and Ansell, 2020; Morales, Gendron and Guénin-Paracini, 2014; Saluja et al , 2021). Nevertheless, it seems safe to say that only rarely is financial statement fraud the desired end-result of its perpetrators.…”
Section: Developing the Mechanics Of The Embezzler Testmentioning
confidence: 99%
“…Hospice fraud is an especially egregious type of healthcare fraud because it diminishes the provision of care for individuals facing the end of life and their grieving families. Often, fraud is a crime fueled by greed and perpetrated to gain unlawful benefits or payments, most often from publicly funded third-party payers (Cheliatsidou et al, 2023; Federal Bureau of Investigations, 2023).…”
Section: Introductionmentioning
confidence: 99%